Identification and Evaluation of Regulatory Role of miR164b in Malaysian Rice Variety (MR303) under Drought Stress: Identification and Evaluation of Regulatory Role of miR164b - Catherine Han Yong Xin; Chee Teng Chay; Abdul Fatah (Journal of Tropical Life Science, 2023)
MR303 is a newly released Malaysian rice cultivar that comes with special traits as it can be cultivated in less fertile soils. Previous studies stated that miR164b is a key molecule that is responsible for regulating drought stress tolerance in many rice varieties. Thus, this study aims to identify the presence and regulatory role of miR164b in the MR303 variety using both computational and experimental approaches. The stem-loop structure of miR164b (pre-miR164b) was identified through reverse-transcriptase PCR (RT-PCR) with a size of ~ 100 bp. The target prediction by psRNA target revealed that the target gene of miR164b is the NAM protein of the NAC transcription factor. A gene expression study by RT-PCR followed by Image J analysis in both control and drought-treated plants demonstrated low expression of miR164b was observed in the drought sample, which led to the accumulation of its target, NAM1. This study provides preliminary knowledge of the presence of miR164b and its regulatory role in the MR303 rice variety.